Last Glacial - Holocene climate variability in the Atlantic sector of the Southern Ocean. (1st March 2016) - Xiao, Wenshen; Esper, Oliver; Gersonde, Rainer
Abstract: The Southern Ocean plays a major role in the glacial/interglacial global carbon cycle. However, there is a substantial lack of information from its Antarctic Zone south of the Polar Front (PF) to understand key climate processes (e.g., sea ice variability, productivity changes, CO2 source region, shifts of the Southern Westerly Wind) active in this region during the glacial/interglacial transition, due to the limited high-resolution sediment records from this area. To close this gap, we investigated high resolution diatom records from a series of sediment cores from the Atlantic and Western Indian sectors of the Southern Ocean between the modern PF and the Winter Sea Ice (WSI) edge. Summer Sea Surface Temperature (SSST) and sea ice information spanning the past 30 thousand years were derived from diatom transfer functions and indicators, which augment comprehensive information on past surface ocean conditions and related ocean and atmospheric circulation, as well as opal deposition. These complementary lines of evidences also provide important environmental boundary conditions for climate simulations understanding the past climate development in the high latitudes Southern Ocean. Our reconstructions show that the Last Glacial (LG) SSSTs south of the modern PF are 1–3 °C colder than modern conditions, WSI expanded to the modern PF. Our data suggests effective carbon export in the Antarctic Zone during the LG. Deglacial two steps of warming support the bipolar seesaw mechanism. Antarctic Zone is an important source region for the CO2 deglacial increase. The warming was more suppressed towards south, due to continuous ice discharge from Antarctica. The SSSTs exceeded modern values during the early Holocene optimum, when WSI extent probably retreated south of its modern position. The southern boundary of maximum opal deposition zone may have shifted to south of 55°S in the Bouvet Island area at this time. The mid-late Holocene cooling with WSI re-expanding to the Bouvet Island area, probably related to enhanced cold-water export by the Weddell Gyre from the developing cavity under the West Antarctic Ice Shelf. The cooling also suggests a northward shift of the Southern Westerly Wind, at least its southern boundary. Highlights: Spatial and temporal variability of sea surface conditions in the Atlantic Antarctic Zone for the past 30 ka. South Atlantic Antarctic Zone is a source region of deglacial CO2 rise. More persistent deglacial cold conditions in the south is related to the continuous ice discharge from Antarctica. Mid-late Holocene cold water expansion is attributed to the developing cavities under the West Antarctic Ice Shelf.